2012
DOI: 10.4149/bll_2012_007
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrence rate in patients with DCIS

Abstract: Abstract:Objectives: The aim of this observational retrospective study was to evaluate the local recurrence rate of ductal carcinoma in situ of the breast (DCIS) and/or invasive breast cancer in patients with DCIS or microinvasive carcinoma of the breast after breast conserving or radical surgery. Secondary aim of the study was comprehensive assessment of the whole management of DCIS and its comparison with European guidelines. Methods: The study was performed in a group of 41 women with DCIS or microinvasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…They followed up on 41 patients with DCIS or DCIS-MI after BCS and mastectomy, and finally, only 27 patients completed the followup. There is no local recurrence occurred 16 . However, the sample size of this study was small, and no survival www.nature.com/scientificreports/ rate was reported.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…They followed up on 41 patients with DCIS or DCIS-MI after BCS and mastectomy, and finally, only 27 patients completed the followup. There is no local recurrence occurred 16 . However, the sample size of this study was small, and no survival www.nature.com/scientificreports/ rate was reported.…”
Section: Discussionmentioning
confidence: 82%
“…However, considering the good prognosis of DCIS-MI and patients' postoperative life quality, it is worth exploring whether BCS + RT is the best choice for DCIS-MI. At present, there are few studies on the surgical methods of DCIS-MI [16][17][18] . The prognosis of BCS + RT or mastectomy for patients with DCIS-MI is still unclear.…”
mentioning
confidence: 99%
“…Two other large retrospective analyses 26,27 confirmed that breast-conserving surgery plus postoperative radiotherapy was superior to single-breast resection for patients with early breast cancer. At the same time, it was suggested that age < 40 years, multiple foci or centers, vascular tumor thrombus, tumor location in the central area or inner quadrant, and high nuclear grade were high risk factors for the local recurrence of breast cancer.…”
Section: Surgical Operationmentioning
confidence: 93%